Development of Monitoring Technique for Cocoa Pod Borer(Conopomorpha cramerella Snell.) - Endang Sulistyowati; Suryo Wardani; Endang Mufrihati (Indonesian Coffee and Cocoa Research Institute, 2005)
Effectiveness and effiency of CPB control were influenced by the right time of control. To decided this methods, information about CPB infestation was needed. An experiment had been conducted to get a simple and accurate technique for CPB monitoring. The experiment was located in Tirawuta, a smallholder cocoa plantation in Kolaka district, South-East Sulawesi. The evaluated monitoring pods techniques using observing all ripe cocoa pod as standard method, i.e. pod colour changes as an indicator of CPB attack, observation on 100 pods during harvesting, moth trapping and observation on the presence of the holes caused by CPB. The collected data expressed as the percentage of CPB attack and compared with each other. Based on the Chi 2 value and time consumed for monitoring, it could be concluded that the observation of 100 attacked pods during harvesting was the most accurate technique closest to the standard method, with a lowest 2 value and not significantly different to standard method. On the contrary the visual observation on the pod colour showed the less accurate technique with  2 value of 242,25–335,33 followed by the bservation on the present of holes on the pod with  2 value of 243,45–282,87. Furthermore, monitoring technique by moth trapping could not be compared with the other techniques since their unit was unequal. However, no insect could be trapped during a night trapping using either chemical trapping or sticky trap. Development of sticky trap by variation in trap colour could be trapped of CPB moth during more than one week. Red trap was the most interesting (preferred) for the CPB followed by the yellow, white and blue ones. There was significant correlation between number of tree sample and the time needed for observation. Larger size of tree sample consumed a longer time for the observation, but in visual symptom and entry/exit hole observation methods, larger sample size did not significantly influence its accuracy. It’s concluded that both of monitoring technique were not a converge estimation. Key words : Cocoa, cocoa pod borer, Conopomorpha cramerella, Integrated Pest Management, monitoring technique.